2017
DOI: 10.3357/amhp.4830.2017
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Hemodynamics and Executive Function During Exercise and Recovery in Normobaric Hypoxia

Abstract: These results support the influence of PFC oxygenation and perfusion on executive function during exercise and recovery in N and NH.Stavres J, Gerhart HD, Kim J-H, Glickman EL, Seo Y. Cerebral hemodynamics and executive function during exercise and recovery in normobaric hypoxia. Aerosp Med Hum Perform 2017; 88(10):911-917.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Performing a cognitive task after exercise is potentially ideal as it takes advantage of the heightened cortical activity during recovery. Twenty to 30 min of moderate intensity (50-60% VO 2max ) cycling increased post-exercise cortical oxygenation (i.e., activation), which aligned with improvements in post-exercise executive function performance (Stroop task) (Yanagisawa et al, 2010;Stavres et al, 2017;Tsubaki et al, 2018). Increased PFC oxygenation may be indicative of higher cortical activity and, therefore, greater mental effort leading to improved cognitive processes such as working memory and attention (Herold et al, 2018).…”
Section: Brain Blood Flow and Oxygenationmentioning
confidence: 86%
See 1 more Smart Citation
“…Performing a cognitive task after exercise is potentially ideal as it takes advantage of the heightened cortical activity during recovery. Twenty to 30 min of moderate intensity (50-60% VO 2max ) cycling increased post-exercise cortical oxygenation (i.e., activation), which aligned with improvements in post-exercise executive function performance (Stroop task) (Yanagisawa et al, 2010;Stavres et al, 2017;Tsubaki et al, 2018). Increased PFC oxygenation may be indicative of higher cortical activity and, therefore, greater mental effort leading to improved cognitive processes such as working memory and attention (Herold et al, 2018).…”
Section: Brain Blood Flow and Oxygenationmentioning
confidence: 86%
“…Upon cessation of low-moderate intensity aerobic exercise, cerebral oxygenation remains elevated for up to 30 min (Faulkner et al, 2016;Stavres et al, 2017;Tsubaki et al, 2018). Performing a cognitive task after exercise is potentially ideal as it takes advantage of the heightened cortical activity during recovery.…”
Section: Brain Blood Flow and Oxygenationmentioning
confidence: 99%
“…A previous study indicated that alteration in CBF, assessed by MCA blood flow velocity, was not directly associated with alteration in cognitive performance during exercise under hypoxia. 22,23 However, CBF is heterogeneously distributed in the brain under severe hypoxia. 84,85 In contrast, during exercise, increases in cerebral metabolism increase CBF to maintain oxygen delivery for aerobic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In follow-up studies, Komiyama et al 21 reported cognitive improvement in the GNG and spatial delayed response tasks during moderate exercise in moderate hypoxia and severe hypoxia. 22 Seo and colleagues [23][24][25] examined the combined effects of moderate exercise and in severe hypoxia in both male 23,24 and female 23,25 participants. The same group reported cognitive improvement in memory [23][24][25] and mathematical performance, 23 but not in the GNG task.…”
Section: Laboratory Settingmentioning
confidence: 99%
See 1 more Smart Citation